How can the loggerhead sea-turtle survive? Exploring the journeys of the Caretta caretta using ANT and critical realism. (November 2017) - O'Mahoney, Joe; O'Mahoney, Hannah; Al-Amoudi, Ismael
The endangered loggerhead sea-turtle ( Caretta caretta ) nests on the shores of the Mediterranean, but faces threats to its existence from a variety of sources. Answering the question of how this species can survive is complex as it involves examining the relationships between the turtle, its natural environment, local tourists, property developers, conservation organisations, governments and law-makers. We argue that actor-network theory provides a powerful methodology for tracing these relations and identifying crucial actors which enable the survival of this animal. Using a rich ethnography and drawing on insights from 116 interviews, we trace three actor-networks that highlight factors important to the survival of the species. Yet, we also highlight the conceptual difficulties that result from using an actor-network theory ontology for understanding socio-ecological interactions and argue that these may be ameliorated by embedding the actor-network theory methodology within a critical realist ontology. We argue that this engagement between critical realism and actor-network theory offers researchers a powerful method for understanding relations between socio-ecological actors while overcoming some of the theoretical difficulties of actor-network theory.